Afghanistan's humanitarian crisis and its impacts on the mental health of healthcare workers during COVID-19 - Zarmina Islam; Aiman Rija; Parvathy Mohanan; Khulud Qamar; Kainat Jahangir; Faisal A. Nawaz; Mohammad Yasir Essar (Cambridge Prisms: Global Mental Health, 2022)
Afghanistan's humanitarian crisis has severely impacted the mental health of frontline workers. With the introduction of the Taliban government, ongoing civil unrest, and other forms of violent attacks, healthcare workers (HCWs) continue to provide patient care despite minimal resources. A severe contraction in the economy, poor supply of medications, political turmoil, and insufficient humanitarian aid have added to pre-existing problems. High levels of insecurity and instability as well as decades of traumatic experiences have contributed to increasing mental health challenges amongst frontline workers. Despite the scarcity of mental health services, HCWs continue to persevere with their service to the community. However, inadequate interventions may have serious implications for HCWs bearing the brunt of multiple traumas. Thus, governmental and international involvement is needed to address both the economic and psychological needs of HCWs in Afghanistan.